No steps behind : Beate Sirota Gordon's battle for women's rights in Japan - Gottesfeld, Jeff (Berkeley : Creston Books, 2019)
"Her parents moved her from Austria to Tokyo, Japan before she started school. They were all rendered stateless when Nazi Germany and Austria stripped Jews of their citizenship. She graduated high school fluent in Japanese plus four other languages and went to college in America at age 15. Cut off from her parents by the Japanese attack on Pearl Harbor, and America's entry into World War II, she went years not knowing if they were alive. She returned to post-war Japan as an interpreter, found her parents, and wrote the fateful words that make her a storied feminist hero in that nation even today. As Justice Sonia Sotomayor said about Beate Sirota Gordon, 'It is a rare life treat for a Supreme Court Justice to get to meet a framer of a Constitution. It is rarer indeed for that framer to have been a woman'"--